The Effect of Different MEdia Thickness and Dosage of Coconut Drugs on the Growth of Biomass of Silk Worm (Tubifex sp) - Sascia Nabilah; Nuraini Nuraini; Sukendi Sukendi (Jurnal Akuakultur SEBATIN, 2022)
This study was to determine the effect of medium thickness and fermented coconut dregs on biomass of silkworms (Tubifex sp.). This research was conducted in January - March 2021 at the Laboratory of Fish Hatchery and Breeding, Faculty of Fisheries and Marine Affairs, University of Riau. The method used in this study was two-factors Completely Randomized Design (CRD) with ten treatments and three replications. The treatments in this study were K1D40 (1cm media thickness at, 40% coconut pulp dregs dose), K1D30 (1cm media thickness at, 30% coconut pulp dregs dose), K1D20 (1cm media thickness at, 20% coconut pulp dregs dose), K1,5D40 (1.5cm media thickness at, 40% coconut pulp dregs dose) K1D30 (1.5cm media thickness 30% coconut pulp dregs dose) K1,5D20 (1.5cm media thickness 20% coconut pulp dregs dose) K2D40 (2cm medium thickness coconut pulp dregs 40% dose) K2D30 (2cm media thickness dose 30% coconut pulp dregs) K2D20 (2cm media thickness with 20% coconut pulp dregs). The best results were obtained in the K2D20 treatment (2cm media thickness, 20% coconut pulp dregs) which resulted in population growth of 4591 ind., growth of biomass of Tubifex sp. worms. K2D20 with a yield of 14.54 g, the highest length increase in the K2D20 treatment was 2.38 cm, the temperature during the study ranged from 26°C - 28°C, pH 6 – 7, dissolved oxygen (DO) ranged from 7.6 ppm – 8.4 ppm and the water discharge ranges from 0.05 to 0.1 liters/sec